Theater in the Bush: Art, Politics, and Community in the Bahamas - Strachan, Ian Gregory (Social justice, 2007)
Part of a special issue on the relationship between art, identity, and social justice. The writer traces the history of the Track Road Theater Company, which he established in the Bahamas in 1996. He discusses the expectations, successes, and failures of the company's first decade in operation; maps his own development as a playwright and artist; and provides a critical look at the cultural development and the politics of identity in the Bahamas since it became independent from Great Britain in 1973. He observes that operating an amateur theater company with anti-establishment leanings in the small island society of the Bahamas has been an education in censorship, class dynamics, systematic neglect, general indifference, and pragmatism. He notes, however, the success of a 2006 production that achieved true popularity; it was completely uncontroversial.